2010
DOI: 10.1096/fj.10-166090
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex analysis of age-related protein and lipid modifications in human Bruch's membrane

Abstract: Aging of the human retina is characterized by progressive pathology, which can lead to vision loss. This progression is believed to involve reactive metabolic intermediates reacting with constituents of Bruch's membrane, significantly altering its physiochemical nature and function. We aimed to replace a myriad of techniques following these changes with one, Raman spectroscopy. We used multiplexed Raman spectroscopy to analyze the age-related changes in 7 proteins, 3 lipids, and 8 advanced glycation/lipoxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 57 publications
1
44
0
Order By: Relevance
“…10,11,14,18,20 Age-related changes within BM occur several decades before cellular ones, thus suggesting that BM dysfunction can precede and may induce changes in surrounding cells. 14,15,19,20 In our system, previously developed to isolate the effects of basement membrane aging from the effects of cellular aging, we have shown that BM aging affects proper attachment and proliferation of RPE cells and increases their rate of apoptosis while decreasing the rate of phagocytosis. 27,28 We have also shown that reengineering human BM can improve the attachment, survival, and proliferation of the RPE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11,14,18,20 Age-related changes within BM occur several decades before cellular ones, thus suggesting that BM dysfunction can precede and may induce changes in surrounding cells. 14,15,19,20 In our system, previously developed to isolate the effects of basement membrane aging from the effects of cellular aging, we have shown that BM aging affects proper attachment and proliferation of RPE cells and increases their rate of apoptosis while decreasing the rate of phagocytosis. 27,28 We have also shown that reengineering human BM can improve the attachment, survival, and proliferation of the RPE.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The disorder is characterized by age-related ultrastructural changes within BM that include diffuse thickening, accumulation of drusen, basal laminar and basal linear deposits, collagen cross-linking in the inner and outer collagen layer, calcification, fragmentation of the elastin layer, and lipidization. [11][12][13][14][15] Cellular changes in advanced AMD include atrophy of the RPE, choriocapillaris and outer retina in nonexudative AMD, and the development of choroidal neovascularization in exudative AMD. [16][17][18] At the current time, any connection between ultrastructural changes observed in BM with age (mentioned above) and cellular changes that develop in AMD is not known.…”
Section: Introductionmentioning
confidence: 99%
“…This suits collagen IV for basement membranes as it allows transfer of nutrients, waste, and cells. With increasing age, there is evidence suggesting dysregulation of collagen IV content within Bruch’s membrane as well as its accumulation in basal laminar deposits(Beattie et al, 2010; Chen et al, 2003; Marshall et al, 1994; van der Schaft et al, 1994). …”
Section: Discussionmentioning
confidence: 99%
“…Instrumental and methodological details have been published elsewhere (Cundy et al, 2015, Gamsjaeger et al, 2011a, Gamsjaeger et al, 2013, Gamsjaeger et al, 2010, Gamsjaeger et al, 2014a, Gamsjaeger et al, 2014b, Gamsjäger et al, 2009, Hofstetter et al, 2012). In the bone blocks, 600 individual measurements (each covering an area of ~ 1 × 1 μm) were obtained in randomly selected areas of interstitial bone, and the following Raman parameters calculated (Gamsjaeger et al, 2014b, Gamsjäger et al, 2009, Gamsjaeger et al, 2011b, Morris and Mandair, 2011): i) the mineral/matrix ratio (MM), ii) the relative proteoglycan content (PG), iii) the maturity/crystallinity (MMC) of the mineral crystallites, and iv) the relative content of two advanced glycation endproducts (AGEs), namely CML (ε- N -carboxymethyl- l -lysine) and PEN (Pentosidine) (Beattie et al, 2010, Beattie et al, 2011, Glenn et al, 2007, Pawlak et al, 2008). Pyrophosphate (PP) presence and spatial quantification in the bone tissue was determined using the Raman band around 360 cm − 1 (Chen et al, 2009, Cheng et al, 2009, Fuerst et al, 2010), normalized to mineral content (based on the v 2 PO 4 band), by RS imaging (210 × 130 μm areas) of open osteons.…”
Section: Methodsmentioning
confidence: 99%